The Investigation of Constraints Faced by Parents in Introducing English to Young Learners: A Descriptive Study - Aeni, Nur; Limbong, Sunarlia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
An increasingly popular practice in education across the globe is teaching young students a second language, primarily English. This study investigates the various constraints and challenges encountered by parents as they endeavor to introduce English to their young children. The research aims to shed light on the multifaceted factors that influence language learning in early childhood. This research was conducted qualitatively by using research instruments in the form of interviews with 8 parents as of data collection. This study categorizes several constrains faced by parents in the context of teaching their children English. The results draw attention to a number of important limitations, parents faced some constrains, such as lack of English skill, limited exposure to English, time constrains, cultural barriers, and financial constrain. In addition, parental time limits, restricted access to good language resources, socioeconomic variables, and varying parental language skill levels. The study also explores psychological barriers such as parents' fears of bilingualism, worries about confusing their kids, and misunderstandings regarding early language acquisition.